ANALISIS KOMPARATIF KELAYAKAN USAHATANI PEMBIBITAN TOMAT (Lycopersicon esculentum Mill) VARIETAS SERVO DAN LARISA DI DESA BANYUKUNING KECAMATAN BANDUNGAN KABUPATEN SEMARANG - Nika Shella Agustin; Renan Subantoro; Rossi Prabowo (MEDIAGRO, 2019)
ABSTRACT Horticultural crops are that have great prospects subsectors, due to their high demand and relatively high commercial value. The purposes of this research were to determine revenues, incomes, RC Ratios, and to compare the income levels and RC Ratios of seedling both Varieties of Servo and Larisa. The research method used in this research was a descriptive analytical method, and the sampling method applied to it was a purposive sampling. This research was conducted in the Banyukuning Village, Bandungan District, Semarang Regency. Fifteen respondents were taken in this research and using the census method, all of these respondents were farmers who were actively seedling tomato. The data was obtained from primary and secondary data by conducting observation, interview, questionnaire, documentation, recording, and literature review. The analytical methods used feasibility analysis and statistical analysis (independent sample t-test). The analysis showed that Servo succeeded to obtain revenue of Rp.4,971,400.- while Larisa gained Rp.1,369,000.-. In relation to income, the first variety reached Rp.1,938,048.18, while the later earned Rp.519,438.39. Additionally, the value of R/C of Servo variety was 1.62, while that of Larisa variety was 1.55. Between Servo and Larisa Varieties in terms of revenue there is significant difference, while in terms of the value of R/C there is no significant difference. Key words: Seedling, Revenue, income, Feasibility, comparisons.